Implementation of Cardiac Troponin I as A Sensitive Biomarker for Myocardial Injury in Animals: Review Article - Tharwat, Mohamed; Marzok, Mohamed (Journal of applied veterinary sciences, 2024)
A biomarker is defined as a detectable biomarker of a specific state and is often measured in urine, blood, milk, sweat, tear or soft tissue, either in physiological or pathological conditions. Of these commonly used biomarkers specifically for heart injury, there are cardiac troponin I (cTnI) and N-terminal pro-B-type natriuretic peptide. The cardiac troponin I is a sensitive biomarker formed by the injured cardiac cells and hence is used in humans for the early discovery of cardiac injury, and in parallel, it is used for prognostic purposes. Veterinary medicine widely uses cTnI as a marker for myocardial injury. In equines, cTnI was found to be a useful marker for the diagnosis of either primary or secondary myocardial injuries. It has also been used in newborn dogs to predict hypoxia and cardiac injury as a result of perinatal asphyxia. In neonatal calves with congenital heart anomalies, it was reported that the affected animals had a higher concentration of cTnI. In lambs with myocarditis, it was reported that significant levels of serum cTnI were detectable in diseased cases compared to healthy ones. This review article was written to emphasize the clinical significance of cTnI as a sensitive biomarker for cardiac injury in animals either in physiological or pathologic states. It has been concluded from several pathological and physiological studies that cTnI is a highly specific cardiac biomarker. It can detect myocardial injury due to primary cardiac disorders such as pericarditis, endocarditis and myocarditis. Also, it can predict cardiac injury in some non-cardiac-affected cases that can affect the heart, such as racing competitions, long road transportation, extensive training, difficult parturition, Downer syndrome, general anesthesia, infestation with external parasites such as ticks, calcium injection in extremely high doses, injection of cardiac glycosides, and use of the electroejaculation method to collect semen.